DSM Manufacturing: When Network Analysis Meets Business Reality. Issue 1 (1st November 2018) - Macdonald, John R.; Sakai, Kelvin
Abstract : DSM Manufacturing has been around for 100 years. In that time, the company has grown considerably in size and is now a global enterprise. With the global expanse, DSM is now facing new challenges, leaving executives to determine what the next steps are in running an efficient supply chain, those that a network analysis will not necessarily address. This case illustrates DSM's process